“Ocean Optimism” and Resilience: Learning From Women’s Responses to Disruptions Caused by COVID-19 to Small-Scale Fisheries in the Gulf of Guinea - Okafor-Yarwood, Ifesinachi Marybenedette; van den Berg, Sayra; Collins, Yolanda Ariadne; Sefa-Nyarko, Clement (Frontiers in Marine Science, 2022)
This study examines the response of women to disruptions caused by COVID-19 in small-scale fisheries (SSF) in the Gulf of Guinea (GOG). It interrogates the concept of resilience and its potential for mitigating women’s vulnerability in times of adversity. We define resilience as the ability to thrive amidst shocks, stresses, and unforeseen disruptions. Drawing on a focus group discussion, in-depth interviews with key informants from Cote d’Ivoire, Ghana and Nigeria, and a literature review, we highlight how COVID-19 disruptions on seafood demand, distribution, labour and production acutely affected women and heightened their pre-existing vulnerabilities. Women responded by deploying both negative and positive coping strategies. We argue that the concept of resilience often romanticises women navigating adversity as having ‘supernatural’ abilities to endure disruptions and takes attention away from the sources of their adversity and from the governments’ concomitant failures to address them. Our analysis shows reasons for “ocean optimism” while also cautioning against simplistic resilience assessments when discussing the hidden dangers of select coping strategies, including the adoption of digital solutions and livelihood diversification, which are often constructed along highly gendered lines with unevenly distributed benefits.